Visions of the Re-Established State of Lithuania in the Deliberations of Expatriate Political Organizations - Banionis, Juozas (History / Istorija, 2024)
Abstract. The article is devoted to defining the possible political contours of the restored Lithuanian state. They are drawn following the traces of the deliberations of the main organizations of the Lithuanian diaspora that existed in the West in the last century (1940–1994). The author includes the Lithuanian Council of America, the Supreme Committee for the Liberation of Lithuania, the Lithuanian Freedom Committee, and the World Lithuanian Community as the main organizations of our diaspora.